Influence of Teachers, Methodology and Content of Physical Education Classes in the Perception of Chilean Students - Giakoni-Ramírez, Frano (2021)
Introduction. The relevance of education in today’s society is evident; therefore, it is of vital importance to know the perception of the various actors that interact in it, in particular, the perception of students about the methodologies and contents offered by the teacher is a determining factor in the teaching-learning process. Objective. To know the students’ perception from three educational centers of the Valparaíso Region (Chile) in relation to the satisfaction with sports activities, the Physical Education class, and the teacher’s role. Methodology. A scale of 12 items grouped in three dimensions was used. A perception scale was applied to a sample of 660 students of 7th (NB5) and 8th (NB6) grades of General Basic Education, belonging to three Chilean educational establishments (municipal, subsidized, and private schools). Results. It is proved that the variables sex and schooling center significantly influence the students’ perception of the subject. Conclusion. These results seek to improve the actions of the different agents involved in the educational process, aimed at improving students’ perception in order to reinforce sports and healthy lifestyle habits.